2022
DOI: 10.3390/coatings12020239
|View full text |Cite
|
Sign up to set email alerts
|

Waste Biopolymers for Eco-Friendly Agriculture and Safe Food Production

Abstract: This work addresses environmental problems connected with biowaste management, the chemical industry, and agriculture. These sectors of human activity cause greenhouse gas (GHG) emissions in the air, climate change, leaching of excess mineral fertilizers applied to soil into ground water, and eutrophication. To mitigate this problem in agriculture, controlled release fertilizers (CRFs) are made by coating mineral fertilizers granules with synthetic polymers produced from the fossil-based chemical industry. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The results of the spinach study [25] showed no statistically significant differences by the substrate treatments compared to the control substrate in leaves and roots weight. The neat SPC and SPC-urea pellets gave significantly the highest leaf chlorophyll content, compared to the control substrate.…”
Section: Spinacia Oleracea L "Gigante D'inverno"mentioning
confidence: 80%
See 4 more Smart Citations
“…The results of the spinach study [25] showed no statistically significant differences by the substrate treatments compared to the control substrate in leaves and roots weight. The neat SPC and SPC-urea pellets gave significantly the highest leaf chlorophyll content, compared to the control substrate.…”
Section: Spinacia Oleracea L "Gigante D'inverno"mentioning
confidence: 80%
“…Two other studies carried out for the cultivation of spinach [25] and oil seed rape [10] have disclosed other important effects of SBS, which are associated to the bio-stimulant properties.…”
Section: Other Effects Of Sbs In Agriculture: Healthy Plants and Food...mentioning
confidence: 99%
See 3 more Smart Citations